Characteristics of Sweet Bread with Substitution of Mocaf Flour and Variation of Cilembu Sweet Potato and Yellow Pumpkin Puree - Septiana Devi; Merkuria Karyantina; Nanik Suhartatik (Fakultas Sains dan Teknologi Unisri, 2026)
Bread is a food that is favored by various groups of people. Wheat flour is the main raw material in making sweet bread. Wheat flour is made from wheat, to reduce wheat imports, wheat flour needs to be replaced with other alternative ingredients. Cilembu sweet potato is one of the sweet potato plants that has the potential to be developed in Indonesia because it is abundant and has good nutritional content. Sweet potato cilembu contain high beta carotene that can be used as a functional food. Pumpkin contains quite complete nutrients, especially beta-carotene content and relatively cheap prices. The high content of dietary fiber in cilembu sweet potatoes and pumpkin is very beneficial for digestion. The purpose of this study was to determine the chemical, physical and organoleptic characteristics of sweet bread that is high in beta carotene and fiber. This study used a factorial completely randomized design (CRD) with the first factor being the ratio of wheat flour and mocaf flour (90:10), (80:20), (70:30). The second factor the ratio of cilembu sweet potato: pumpkin (60:40), (50:50), (40:60). The results showed sweet bread with the highest levels of beta-carotene and fiber in the ratio of 70% wheat flour: 30% mocaf flour, 40% cilembu sweet potato: 60% pumpkin respectively at 6.47% and 12.9%. Sweet bread formulation favored by panelists in the ratio of 90% wheat flour: 10% mocaf flour, 60% cilembu sweet potato: 40% pumpkin at acore 4.09 (liked).